NCOG-10. RELATIONSHIP BETWEEN COGNITIVE FUNCTION, MOOD, AND FUNCTIONING IN GLIOMA SURVIVORS - Van Dyk, Kathleen (Neuro Oncol, 2019)
Ensuring optimal quality of life and functioning is a clinical priority in treating glioma survivors. Cognitive function and mood symptoms are prevalent in this population after treatment and it’s reasonable to consider these as significant contributors to patients’ functioning at work and in daily life. However, it’s unclear the degree to which these symptoms contribute to such outcomes. To address this question, we examined the relationships between cognitive tests (i.e., a neuropsychological battery) and mood measures (i.e., the Beck Depression Inventory-II, and the Beck Anxiety Inventory) and work and daily functioning (i.e., Work Productivity and Activity Impairment Questionnaire). Partial correlation of cognitive tests and regression models also included age and IQ (i.e., Test of Premorbid Functioning). Of the 11 participants who were currently working, worse work productivity was significantly associated with worse processing speed (Stroop color naming r=-.74,p=.03, Stroop color word r=-.78,p=.02). Similarly, worse ability in daily activities was also associated with worse processing speed and executive function (Stroop color naming, r=-.52,p=.04; Stroop color word, r=-.55,p=.03; Trails B, r=-.53,p=.03). Greater depression symptoms were strongly correlated with both worse work productivity (r=.83,p=.002), and worse ability in daily activities (r=.55,p=.01). Depression symptoms were generally uncorrelated with cognitive scores. In linear regression models that included both depression symptoms and cognitive scores, only depression emerged as a significant predictor of work productivity and ability to conduct daily activities. In sum, glioma survivors face multiple threats to work and daily functioning by way of tumor and treatment related symptoms. Our analyses suggest that both cognitive function and mood symptoms are important to consider in optimizing functioning, but depression appears to vastly outweigh cognitive function in this regard. These preliminary findings highlight the importance of careful attention to these symptoms in survivorship and point to future research directions elaborating on these relationships.